Prevalence of breastfeeding up to the sixth month of the infant’s life and its association with breastfeeding self-efficacy and the perceived experience of the implementation of the Baby-Friendly Hospital Initiative’s 10 Steps for Successful Breastfeeding - Economou, Mary (My University, 2018)
Breastmilk is the ideal source of infant nourishment. However, exclusive breastfeeding (EBF) for the first six months, as recommended by the WHO, remains relatively low even after three decades of international and national initiatives for the promotion of breastfeeding. While the effectiveness of the Baby-Friendly Hospital (BFH) Initiative’s “Ten Steps for Successful Breastfeeding” has been documented, there is often suboptimal implementation. No hospital in Cyprus has BFH certification and there is only anecdotal evidence with regards to the implementation of the 10 steps and the International Code for the Marketing of Breastmilk Substitutes (ICMBS). Furthermore, the only data for breastfeeding is restricted to the first 48 hours. Low maternal breastfeeding self-efficacy (BFSE), which is influenced by maternity care practices, contributes to the premature discontinuation of breastfeeding.
Επιπολασμός του μητρικού θηλασμού μέχρι τον έκτο μήνα της ζωής του παιδιού και συσχέτιση με την αντιλαμβανόμενη αυτοπεποίθηση για μητρικό θηλασμό και την αυτοαναφερόμενη εφαρμογή των ’10 βημάτων για επιτυχή θηλασμό’ στα μαιευτήρια της Κύπρου
Keywords: Breastfeeding; Exclusive Breastfeeding; Maternal Breastfeeding Self-Efficacy; 10 Steps to Successful Breastfeeding; Infant Care Social Support; Workplace Breastfeeding Social Support